2021
DOI: 10.1097/md.0000000000027437
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-10 -819C/T, -592A/C polymorphisms with the risk of preeclampsia

Abstract: Objective: The purpose of our study was to investigate whether IL-10 -819C/T, -592A/C polymorphisms were associated with preeclampsia (PE) susceptibility.Methods: A comprehensive and systematic literature search was performed through online databases, including Web of Science, PubMed, EMBASE, and Chinese databases. Then eligible literatures were included according to inclusion criteria and exclusion criteria. Statistical data analysis was performed using Stata 10.0 software. Odds ratios (OR) and 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Among the genes reported to be associated with preeclampsia are MTHFR (rs1801133), F5 (rs6025) [10], NOS3 [11], PPARγ [12], ERAP2 [13], STOX1, CORIN, EPHX1, INO80B [14], GSTP1 [15], FGF5 [16], a role for the X chromosome [17] and several other chromosomal regions. According to this set of studies, some genes were found to affect susceptibility to preeclampsia in specific populations [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Among the genes reported to be associated with preeclampsia are MTHFR (rs1801133), F5 (rs6025) [10], NOS3 [11], PPARγ [12], ERAP2 [13], STOX1, CORIN, EPHX1, INO80B [14], GSTP1 [15], FGF5 [16], a role for the X chromosome [17] and several other chromosomal regions. According to this set of studies, some genes were found to affect susceptibility to preeclampsia in specific populations [18,19].…”
Section: Introductionmentioning
confidence: 99%